The effects of Raise, Activate, Mobilise and Potentiate (RAMP) warm-up protocol on futsal performance / Ahmad Amirul Mukminin Roslan ... [et al.]. - Roslan, Ahmad Amirul Mukminin; Mohamed, Muhamad Noor; Md Radzi, Noor Azila Azreen; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Shari, Maisarah; Raja Hussain, Raja Nurul Jannat (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The RAMP warm-up protocol, combining aerobic activity, flexibility, and sport-specific exercises, is underutilized in futsal despite its potential benefits [1,2,3]. This study examines its impact on speed, agility, and endurance in male futsal players, addressing gaps in conventional warm-up practices. Sixteen male futsal players, selected via purposive sampling, performed RAMP and traditional warm-up protocols. Speed was assessed using a 20-meter sprint test, agility with the T-test, and endurance through the Yo-Yo Intermittent Recovery Test. The RAMP protocol included raising (5 minutes), activating and mobilizing (5 minutes), and potentiating (10 minutes) phases to optimize performance metrics.